Enhancing venetoclax efficacy in leukemia through association with HDAC inhibitors - Jorge Antonio Elias Godoy Carlos; Mauricio Temotheo Tavares; Keli Lima; Larissa Costa de Almeida; Karoline de Barros Waitman; Leticia Veras Costa-Lotufo; Roberto Parise-Filho; João Agostinho Machado-Neto (Cell Death Discovery)
Abstract Epigenetic modifications significantly influence gene expression and play crucial roles in various biological processes, including carcinogenesis. This study investigates the effects of novel purine-benzohydroxamate compounds, particularly 4  f, as hybrid kinase/histone deacetylase (HDAC) inhibitors in hematological malignancies, focusing on acute myeloid leukemia (AML). Our results demonstrate that these compounds selectively reduce cell viability in blood cancer cells, with inhibitory concentration values indicating higher potency against neoplastic cells compared to normal leukocytes. Mechanistically, 4  f induces apoptosis and cell cycle arrest, promoting differentiation in leukemia cells, while effectively inhibiting HDAC activity. Furthermore, 4  f enhances the therapeutic efficacy of venetoclax, a BCL2 inhibitor, in AML models sensitive and resistant to this drug. The combination treatment significantly increases apoptosis and reduces cell viability, suggesting a synergistic effect that may overcome drug resistance. This study provides valuable insights into the potential of HDAC inhibitors, particularly 4  f, as a promising therapeutic strategy for treating resistant hematological malignancies. Our findings underscore the importance of further exploring hybrid kinase/HDAC inhibitors in combination therapies to improve outcomes in patients with acute leukemias and other hematological malignancies.